Mastering CSS3 colors - Fhala, Ben; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2015)
"Colors have been around the Web since the very early days. Before the birth of CSS, color attributes were baked into HTML or into images. As the Web evolved and moved into a CSS-friendly world, colors were extracted and moved into style files. Colors are at the very heart of display and graphical representations. It's critical for any developer or web designer to understand colors and their relationships in-depth, so that they can be more creative and gain control over the style and design of their websites."--Resource description page.
Title from resource description page (Safari, viewed January 18, 2016).
Presenter, Ben Fhala.
Keywords: Cascading style sheets; Electronic books